2017
DOI: 10.5194/cp-13-1037-2017
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric circulation and hydroclimate impacts of alternative warming scenarios for the Eocene

Abstract: Abstract. Recent work in modelling the warm climates of the early Eocene shows that it is possible to obtain a reasonable global match between model surface temperature and proxy reconstructions, but only by using extremely high atmospheric CO 2 concentrations or more modest CO 2 levels complemented by a reduction in global cloud albedo. Understanding the mix of radiative forcing that gave rise to Eocene warmth has important implications for constraining Earth's climate sensitivity, but progress in this direct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…More recently, Lunt et al (2012) carried out a synthesis of a group of models that had all conducted Eocene simulations (Lunt et al, 2010b;Heinemann et al, 2009;Winguth et al, 2010;Huber and Caballero, 2011;Roberts et al, 2009), with a focus on surface temperatures. Subsequent work also explored the precipitation in the simulations (Carmichael et al, 2016) and the implications for ice sheet growth (Gasson et al, 2014). This was an "ensemble of opportunity" in that the model simulations were carried out independently, using a variety of paleogeographic and vegetation boundary conditions, under a range of different CO 2 concentrations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Lunt et al (2012) carried out a synthesis of a group of models that had all conducted Eocene simulations (Lunt et al, 2010b;Heinemann et al, 2009;Winguth et al, 2010;Huber and Caballero, 2011;Roberts et al, 2009), with a focus on surface temperatures. Subsequent work also explored the precipitation in the simulations (Carmichael et al, 2016) and the implications for ice sheet growth (Gasson et al, 2014). This was an "ensemble of opportunity" in that the model simulations were carried out independently, using a variety of paleogeographic and vegetation boundary conditions, under a range of different CO 2 concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Although both of these studies indicated that clouds could be the key to reconciling proxies and models, neither of the changes applied were physically based. Furthermore, more recent work has indicated that the response to modifying cloud albedo is very similar to that of increasing CO 2 , at least in terms of the meridional temperature gradient (Carlson and Caballero, 2017), such that prescribing cloud changes can result in a system that is somewhat unconstrained. As such, the relevance of these studies for future prediction or to other paleo-time-periods remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Although both of these studies indicated that clouds could be the key to reconciling proxies and models, neither of the changes applied were physically based. Furthermore, more recent work has indicated that the response to modifying cloud albedo is very similar to that of increasing CO 2 , at least in terms of meridional temperature gradient (Carlson and Caballero, 2017), such that prescribing cloud changes can result in a system that is somewhat unconstrained. As such, the relevance of these studies for future prediction or to other paleo time periods remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Climate modeling has been able to reconstruct this pattern with very high pCO 2 levels (up to ∼4500 ppm: Huber and Caballero, 2011), but such extremely elevated pCO 2 is not documented by proxy records. It is therefore assumed that Eocene cli-mate sensitivity-often defined as Earth system sensitivity for longer time scales, including both "fast" and "slow" feedbacks (Lunt et al, 2010)-was elevated compared to present, and/ or that other mechanisms, in addition to the dominant forcing of pCO 2 , were in operation (Caballero and Huber, 2013;Anagnostou et al, 2016;Zeebe et al, 2016;Carlson and Caballero, 2016;Cramwinckel et al, 2018;Keery et al, 2018). A variety of geochemical and biological proxies as well as carbon cycle modeling have been used to estimate Eocene pCO 2 , but these estimates still differ hugely (with values ranging from hundreds to thousands of parts per million pCO 2 ); however, there is some convergence forming (Holdgate et al, 2009;Beerling and Royer, 2011;Foster et al, 2017).…”
Section: Introductionmentioning
confidence: 99%